1994
DOI: 10.1002/eji.1830240725
|View full text |Cite
|
Sign up to set email alerts
|

Covalent binding of C3b to monoclonal antibodies selectively up‐regulates heavy chain epitope recognition by T cells

Abstract: Protein C3 of the complement system is known for its role in the nonspecific immune response. Covalent binding of C3b to antigen upon complement activation also plays a significant role in specific T cell immune response. C3b-antigen complexes can bind to complement receptors on the antigen-presenting cell, and the C3b antigen link (most often an ester link) remains fairly stable inside the cells. In this study, IgG1,kappa and IgG2a,kappa murine monoclonal antibodies (mAb) were used as antigens; covalent compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…The delayed endosomal proteolysis results in an improved peptide loading on MHC class II molecules and an increased stability of these molecules in the lysosomes [105]. Consistent with this observation is the finding that attachment of C3b to the heavy chain of murine IgG results in a 100-fold reduction in the amount of IgG required for human B cell lines to stimulate heavy chain-specific T cell clones, without enhancing antigen presentation to light chain-specific T cell clones [106]. It is noteworthy that CD21 may be able to promote antigen presentation in non-specific B cells, without assistance from BCR [107].…”
Section: The Role Of Cd19/cd21 In B Cell Developmentsupporting
confidence: 71%
“…The delayed endosomal proteolysis results in an improved peptide loading on MHC class II molecules and an increased stability of these molecules in the lysosomes [105]. Consistent with this observation is the finding that attachment of C3b to the heavy chain of murine IgG results in a 100-fold reduction in the amount of IgG required for human B cell lines to stimulate heavy chain-specific T cell clones, without enhancing antigen presentation to light chain-specific T cell clones [106]. It is noteworthy that CD21 may be able to promote antigen presentation in non-specific B cells, without assistance from BCR [107].…”
Section: The Role Of Cd19/cd21 In B Cell Developmentsupporting
confidence: 71%
“…The delayed endosomal proteolysis results in an improved peptide loading on MHC class II molecules and an increased stability of these molecules in the lysosomes [95]. Consistent with this observation is the finding that attachment of C3b to the heavy chain of murine IgG results in a 100-fold reduction in the amount of IgG required for human B-cell lines to stimulate heavy chain-specific T-cell clones, without enhancing antigen presentation to light chainspecific T-cell clones [96]. It is noteworthy that CD21 may be able to promote antigen presentation in non-specific B cells, without assistance from BCR [97].…”
Section: Complement-mediated Promotion Of Antigen Processing and Pressupporting
confidence: 71%
“…It is possible that immune complexes internalized by CD21 are preferentially targeted to certain intracellular compartments. Such a chaperoning role for C3b has been suggested by studies in which certain antigenic epitopes are presented more efficiently when the antigen is covalently linked to C3b [40]. Additional studies demonstrated that C3b-coated antigens are protected from proteolysis by endosoma1 proteases encountered early in the processing pathway, delaying degradation until entry into lysosomal compartments containing proteases which release the antigen from C3b [41].…”
Section: Discussionmentioning
confidence: 98%